Coal and peat fires : a global perspective. - Stracher, Glenn B.; Prakash, Anupma; Sokol, Ellina V. (Elsevier Science, 2010)
Coal and Peat Fires: A Global Perspective is a compelling collection of research conducted by scientists and engineers around the world. The first of four volumes in the collection, Coal - Geology and Combustion, & nbsp;features chapters that discuss the origin of coal and coal fires; mining and use of coal; combustion and coal petrology; environmental and health impacts of coal fires; combustion by-products; geochemical, & nbsp;geophysical, and engineering methodologies for studying coal fires; the control, extinguishment, and political implications of coal fires; and much more. Integrates pioneering coal-fires research, with topical coverage of remote sensing, policymaking, and more Contains hundreds of tables, graphs, and high quality color images with online links to videos and multimedia presentations Serves as an essential guide to the socio-economic and geo-environmental impacts of coal fires.